2015
DOI: 10.1164/rccm.201411-1958oc
|View full text |Cite
|
Sign up to set email alerts
|

Airway Remodeling in Preschool Children with Severe Recurrent Wheeze

Abstract: In preschoolers with severe recurrent wheeze, markers of remodeling and inflammation are unrelated, and atopy is associated with ASM. In the absence of control subjects, we cannot determine whether differences observed in RBM thickness and vascularity result from disease or normal age-related development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 48 publications
4
95
0
1
Order By: Relevance
“…Pre-school children with severe wheezing that developed asthma only had significantly more ASM in their endobronchial biopsies at pre-school age compared with those wheezers that did not develop asthma, while tissue eosinophilia or RBM thickness were not predictors [36]. In addition, increased ASM was the only change associated with atopy in severe pre-school wheezers [31]. Thus, early abnormalities in ASM function may determine asthma development.…”
Section: Airway Smooth Musclementioning
confidence: 93%
See 1 more Smart Citation
“…Pre-school children with severe wheezing that developed asthma only had significantly more ASM in their endobronchial biopsies at pre-school age compared with those wheezers that did not develop asthma, while tissue eosinophilia or RBM thickness were not predictors [36]. In addition, increased ASM was the only change associated with atopy in severe pre-school wheezers [31]. Thus, early abnormalities in ASM function may determine asthma development.…”
Section: Airway Smooth Musclementioning
confidence: 93%
“…Moreover, even younger pre-school children (median age 3 years) with severe recurrent wheezing have evidence of increased RBM thickness and tissue eosinophilic inflammation [5]. Interestingly, a recent biopsy study in pre-school children with severe wheeze has shown the presence of several features of remodelling, including increased RBM thickness, ASM, vascularity and mucus gland area, but no relationship between inflammatory cell counts in biopsies and remodelling [31]. A limitation of human studies, especially paediatric studies, is the relative difficulty in obtaining repeated invasive biopsies to assess longitudinal changes in pathology over time.…”
Section: Limitations Of Therapy Targeted At Inflammationmentioning
confidence: 99%
“…Despite the generally accepted notion of airway inflammation guiding airway remodeling, this association has been disputed based on studies conducted in both children and adults. A study involving pre-school children failed to detect any association between airway inflammation and airway remodeling [96]. In a different study in adults, while allergen exposure induced airway inflammation, bronchoconstriction and airway remodeling, methacholine challenge induced bronchoconstriction and airway remodeling but no airway inflammation [97].…”
Section: Beneficial and Adverse Effects Of Neutrophils In The Asthmatmentioning
confidence: 99%
“…59 Taken together, these findings indicate that airway histopathologic changes and alterations consistent with airway remodeling occur by 3 years of age in children who are destined to have persistent asthma by school age. 60 …”
Section: Airway Physiologic Alterationsmentioning
confidence: 99%